2019
DOI: 10.18203/2394-6040.ijcmph20190190
|View full text |Cite
|
Sign up to set email alerts
|

A study on the work profile of ASHA workers in a district of Odisha in eastern India

Abstract: Background: Our aim was to study the socio demographic determinants of ASHA workers, to study the work profile of the ASHA workers, to assess the knowledge, awareness and practice of their roles and responsibilities in the delivery of health care services and to suggest specific recommendations on the ASHA scheme based on the study findings.Methods: The type of study was a cross sectional study, placed at Khordha district in Odisha. Time Period of this study was March to June 2018. 1218 ASHAs were finally incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
(3 reference statements)
1
5
1
Order By: Relevance
“…Panda et al undertook a study on ASHAs working in some parts of Odisha, and found that 100% of the ASHAs helped in immunization, and 98% of them knew about family planning activities (9). Their observations are similar to that of the current study that majority of the ASHAs (66.5%) have correct knowledge about immunization and family planning.…”
Section: Discussionsupporting
confidence: 84%
“…Panda et al undertook a study on ASHAs working in some parts of Odisha, and found that 100% of the ASHAs helped in immunization, and 98% of them knew about family planning activities (9). Their observations are similar to that of the current study that majority of the ASHAs (66.5%) have correct knowledge about immunization and family planning.…”
Section: Discussionsupporting
confidence: 84%
“…Similar finding was present in Panda et al conducted a study in rural block of Haryana. 13 In contrast of our study done by Kansal et al found that 43.7% of ASHA were from OBC caste. 14 Reason for such finding in our study may be because of recruitment of ASHA was not in accordance with population proportion as recommended in NHM guidelines.…”
Section: Discussioncontrasting
confidence: 76%
“…Several studies have reported that ASHAs are unhappy with the present incentive-based honorariums and are seeking permanent jobs with salaries [ 22 , 24 ]. Non-availability of transport has been described in other studies [ 19 , 25 ], for example, emergency “108” vehicles were often delayed in Orissa [ 25 ]).…”
Section: Discussionmentioning
confidence: 85%